Characterisation of Gold and Sulphides from a High-Grade Zone in the Melville Area, Murchison Domain, Western Australia - Ameen, S.M.; Wilde, Simon; Akter, N. (Unknown, 2012)
The Melville gold prospect lies in the western part of the Archean Yalgoo greenstone belt in theMurchison Domain, Western Australia . The area is known for hosting sub-economic goldmineralisation. Two major styles of gold mineralisation are reported: i) quartz vein-hosted and ii)within sheared mafic, ultramafic rocks and/or banded iron formation and along contacts betweenmafics and felsic porphyries. The present work reports for the first time characteristics of gold andbase metals from a high-grade vein intercepted in drillhole MVRC 054D along the boundarybetween dacite and mafic rock. The study reveals that primary gold occurs within a thin calcite basemetal vein as large grains and is associated with galena, pyrrhotite, pyrite and chalcopyrite.Calcite, epidote, clinozoisite and titanite are the alteration minerals associated with mineralisation.The regional north-sout h trending Noongal shear zone caused juxtaposition of contrastinglithologies along which the influx of metal-enriched hydrothermal fluids appear to have controlledthe gold mineralisation. The present study also indicates that the high-grade zone most probablyrepresents the volatile-rich latter part of an enriched hydrothermal system, the earlier liquid richpart of which is likely to have remained at depth. Therefore, deeper drilling in proximity to theseveins is suggested since it might lead to an increase of the gold resource in the Melville area.